من الانعزال التام إلى الانذماج الكلي: تجربة اليهودية الإصلاحية في المواجهة الحداثة الغربية:(min al- in'izal al-tamm ila indimaj al kulli: tajribat al Yahudiyya al islahiyya fi muwajahat al hadathah al Gharbiyya) - Mohd. Daud, Noor Amali (Academy of Islamic Studies University of Malaysia, 2010)
Current Western civilization is basically founded on rationalist, liberal and secular paradigms, and has been influenced by a certain degree of disenchantment with religion. This has had repercussions for the analysis of social realities as well as for the articulation of religious thought, modern Jewish thought being no exception. This article attempts to explore one of the significant modern movements in Jewish thought, namely Reform Judaism. It investigates the historical circumstances of the emergence of the Reform movement in Jewish socio-religious thought. It also deals with the question how the movement succeeded in shifting the Jewish self-understanding from closed and exclusive paradigms to more open and liberal ones in Germany, in particular, and in other European countries, in general.